Analysis of single layer artificial neural network neuromorphic hardware chip - Pant, Aruna; Kumar, Adesh; Kuchhal, Piyush (Institute of Advanced Engineering and Science, 2024)
The neuromorphic architectures are hardware network systems designed with neural functions. Neural networks seen in biology serve as an inspiration for network systems. A synapse connects every node or neuron in an artificial neural network (ANN) to every other node. As in biological brains, the amplitude of the linking between nodes referred to as synaptic weights will regulate the connection. In contrast to conventional design, ANN uses many highly organized dealing pieces that work together to solve real-world issues. The design of the neuromorphic hardware chip is discussed in the paper. The target device used is a Virtex-5 Field Programmable Gate Array (FPGA) and the simulation is taken on Xilinx ModelSim software. This chip is designed for 20 neuron inputs, each of the neuron inputs is 8-bit. Each 20-neuron input is multiplied by 20 input weights and each weight is 8-bit so when these 20 input weights are multiplied by 20 neuron inputs in the multiplier it gives 16-bit output. A control logic is used in this neuromorphic hardware chip design which is used to feed multiplier output to each input of the hidden layer. The system-level outcome of the hidden layer is then given to the multiplexer which has 20 inputs and one single output. The multiplexer is used to select any of the 20 outputs of the control logic. Finally, to gain an understanding of the performance of this neuromorphic hardware chip, we have computed the hardware utilization parameters. These parameters include slices, input/output blocks (IOBs), registers used, memory, and the overall propagation delay used by the hardware chip.